Gabapentin enacarbil – clinical efficacy in restless legs syndrome - Agarwal, Pinky (Dove Medical Press, 2010)
Restless legs syndrome (RLS) is a sleep-related movement disorder commonly involving an unpleasant urge to move the limbs, typically the legs. Dopaminergic agents represent the first-line therapy for RLS; however, long-term use of such drugs results in worsening symptoms due to “augmentation” or other adverse events. Gabapentin, an analog of the inhibitory neurotransmitter gamma-aminobutyric acid (GABA), is an anticonvulsant/analgesic agent. Gabapentin is only mildly effective in relieving RLS symptoms, perhaps a result of its poor absorption from the gastrointestinal (GI) tract. Gabapentin enacarbil is a prodrug of gabapentin specifically designed to enhance absorption via the GI tract, and hence provide improved circulating levels of gabapentin on metabolism. Clinical trials to date have demonstrated favorable safety and (compared to traditional gabapentin) improved pharmacokinetics and efficacy in treating RLS symptoms. Thus, gabapentin enacarbil may prove to be a useful drug in treating RLS. An application of gabapentin enacarbil for treatment of RLS is currently pending with FDA for approval.